Implementation of the Deferred Prosecution Agreement (DPA) Concept in Handling Corporate Crime in the Laws of Indonesia and Other Countries - Metty Murni Wati Ibrahim; Jovita Irawati; Jamin Ginting; Nelson Pardamean Purba (PT Publikasiku Academic Solution, 2024)
This research uses a normative empirical research method that combines a normative analysis approach with empirical methods to explore certain legal issues that discuss the concept of a Deferred Prosecution Agreement (DPA) as an alternative dispute resolution in corporate crime cases in Indonesia, taking into account the experiences of the United States and the United Kingdom. The main focus is to identify the advantages and disadvantages of DPA implementation in Indonesia, including maintaining corporate reputation, minimizing the risk of bankruptcy, and resolving cases efficiently. The weaknesses of DPA in Indonesia include its vulnerability to abuse of authority and the absence of specific regulations governing its use.